The Assessment of Water Compatibility of Adaptable Stick-Net Cage for Resilience Milkfish Cultivation in Tanjung Mas, Indonesia - Martuti, N. K. T.; Sidiq, W. A. B. N.; Melati, I. S.; Mutiatari, D. P. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
Milkfish cultivation becomes the main livelihood of farmers in coastal areas. However, the land for milkfish cultivation is shrinking due to land use for settlements, industries, and sea-level rise. A Stick-net cage is an aquaculture solution in limited space for an inland fishpond. It can be placed in seashore areas while maintaining the quality of the aquatic environment and nutrient circulation. This study aims to analyze water compatibility in the stick-net cage areas for supporting sustainable aquaculture activities. An exploratory observational study was conducted in Tanjung Mas Village, Semarang, Central Java, Indonesia. Ten sampling areas were determined purposively by considering the point locations toward household wastewater and industrial outfalls. Based on these criteria, the ten stations used as sample areas were divided into industrial outfall areas (1st – 5th station) and areas close to the open sea (6th – 10th station). Physical parameters in the sampling areas, including temperature, water-current, turbidity, and clearness, met seawater standards for milkfish cultivation. Chemical indicators, such as NH4 and P in water, were very high, which may be caused by domestic and industrial waste contamination and increased organic fermentation activity on the seabed. However, the existing stick-net cages have exceeded the capacity of the coastal water areas. In general, the physicochemical parameters in the Tanjung Mas water area are suitable for milkfish cultivation. However, it is necessary to reduce the amount of pond density to give growth space for milkfish. In addition, wastewater management and treatment plants should be built up to reduce water contamination.